2011
DOI: 10.1007/s10529-011-0825-z
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular protease in Actinomycetes culture supernatants inhibits and detaches Staphylococcus aureus biofilm formation

Abstract: Bacterial biofilms are associated with chronic infections due to their resistance to antimicrobial agents. Staphylococcus aureus is a versatile human pathogen and can form biofilms on human tissues and diverse medical devices. To identify novel biofilm inhibitors of S. aureus, the supernatants from a library of 458 Actinomycetes strains were screened. The culture supernatants (1% v/v) of more than 10 Actinomycetes strains inhibited S. aureus biofilm formation by more than 80% without affecting the growth. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…S. aureus biofilm formation, however, is susceptible to proteinase K28. With HI B. bacteriovorus HD100 cultures releasing proteases into the media, we were intrigued by the idea that this predator and its secreted hydrolytic enzymes may block biofilm formation by S. aureus .…”
Section: Resultsmentioning
confidence: 99%
“…S. aureus biofilm formation, however, is susceptible to proteinase K28. With HI B. bacteriovorus HD100 cultures releasing proteases into the media, we were intrigued by the idea that this predator and its secreted hydrolytic enzymes may block biofilm formation by S. aureus .…”
Section: Resultsmentioning
confidence: 99%
“…The culture supernatants of these biofilm reducing actinomycetes were found to contain a protease which in addition to inhibiting biofilm formation itself also disrupted preestablished biofilm structures. This study by Park et al [31] suggests that protease treatment could be a feasible tool to reduce or eradicate biofilm mediated persistent S. aureus infections [31].…”
Section: Role Of Extracellular Proteases From Other Prokaryotes In DImentioning
confidence: 97%
“…Park et al [31] identified some novel biofilm inhibitors of S. aureus, by screening culture supernatant of 458 actinomycete isolates. The culture supernatants in the ratio of 1% (v/v) of more than 10 Actinomycete isolates inhibited S. aureus biofilm formation by more than 80% without inhibiting growth of the test culture.…”
Section: Role Of Extracellular Proteases From Other Prokaryotes In DImentioning
confidence: 99%
See 1 more Smart Citation
“…This is due, for example, to the production of toxins (Wu et al, 2016). However, the formation of biofilm, a structure formed by a mucopolysaccharide matrix, is still considered one of the main forms of pathogenesis (Paharik e Horswill, 2016;Park et al, 2012).…”
Section: Introductionmentioning
confidence: 99%